Pendidikan Karakter Melalui Peningkatan Kualitas Lulusan SMA - Eko Rubiyanto (Jurnal VARIDIKA, 2019)
This paper aims to describe character education through improving the quality ofhigh school graduates. This type of research is qualitative research. The research subjectsare researchers and research objects of educators and students. Data collection methodsthrough observation, tests and documentation. The data analysis technique was carriedout in a descriptive qualitative manner with a flow model consisting of data collection,data reduction, data presentation, verification and conclusion drawing. The results ofthis study indicate that: (1) Thustworthiness character education by recognizing that thequestions tested are considered difficult so that it needs to study extra hard and smartlike working on HOTS questions, and strict examination supervision in accordance withexisting provisions. (2) Caring character education by celebrating graduation withoutconvoys and scribbles that violates the safety and order of others and distributes fastbreaking takjil for people who are at the intersection of lights on the highway. (3)Respect character education by respecting and respecting the achievement of academic results among students and not doing things that disturb others such as convoys that cause noise. (4) Citizenship character education by celebrating graduates by not violating school rules and not violating road traffic laws. (5) Responsibility character education by waiting for announcements in accordance with school rules, whatever academic results obtained remain grateful and ontinue to the next step by utilizing academic results to the fullest.